The Influence of Environmental Cost Accounting Integration on Profit Margin Optimization in Manufacturing Companies Based on Circular Economy - Amin, M.; Mutira, Putri; Ramandei, Pilipus; Widada, Dharma; Harahap, Subur (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the impact of integrating environmental cost accounting on profit margin optimization in manufacturing companies adopting circular economy principles. As sustainability pressures increase, firms must internalize environmental externalities through proper cost identification, allocation, and reporting. Using a quantitative approach, the study analyzes secondary data from 60 manufacturing firms listed on the Indonesia Stock Exchange from 2019 to 2023 through multiple regression analysis. The key variables include the integration of environmental cost components—prevention, remediation, and disposal—and their influence on gross and net profit margins. Results show a significant positive relationship (p < 0.01), with integration linked to improved efficiency, waste reduction, and profitability.